Robotic Urologic Surgery in Infants: Results and Complications - Kim, Christina (Frontiers in Pediatrics, 2019)
Over the last 30 years, robotic surgery has evolved into the preferred surgical approach for many operative cases. Robotics has been associated with lower pain scales, shorter hospitalizations, and improved cosmesis. However, its acceptance in pediatrics have been hampered by longer operative times, smaller working space, and limited fine surgical instruments. Many find these challenges even more pronounced when performing robotic surgery in infants (i.e. children < 1 year old). Although the data in infants is less robust, many studies have shown benefits similar to the adult population. Specifically, multiple reports of robotic surgery in infants have shown lower postoperative analgesic use. Additionally, hospital stays are shorter, which may lead to quicker return to work for parents and guardians. Multiple reports have shown low complication rates of robotic surgery in infants. When complications have occurred, they are usually Clavien Grade 1 and 2, with occasional grade 3. Often the complications are not from the robotic technique, but are linked to other factors such as the ureteral stents. Most importantly, the success rates of surgery are comparable to open surgery. This chapter will review indications for the most common urologic robotic surgeries performed in infants. Also, we will review reported results and complications of robotic surgery in children, with specific attention to the infant population. However, data focused only on infants is limited. Many studies have some infant patients, but their results are often mixed with all pediatric patients.